The small Ca(2+)-binding protein CSE links Ca(2+) signalling with nitrogen metabolism and filament integrity in Anabaena sp. PCC 7120 - Walter, Julia (BMC Microbiol, 2020)
BACKGROUND: Filamentous cyanobacteria represent model organisms for investigating multicellularity. For many species, nitrogen-fixing heterocysts are formed from photosynthetic vegetative cells under nitrogen limitation. Intracellular Ca(2+) has been implicated in the highly regulated process of heterocyst differentiation but its role remains unclear. Ca(2+) is known to operate more broadly in metabolic signalling in cyanobacteria, although the signalling mechanisms are virtually unknown. A Ca(2+)-binding protein called the Ca(2+) Sensor EF-hand (CSE) is found almost exclusively in filamentous cyanobacteria. Expression of asr1131 encoding the CSE protein in Anabaena sp. PCC 7120 was strongly induced by low CO(2) conditions, and rapidly downregulated during nitrogen step-down. A previous study suggests a role for CSE and Ca(2+) in regulation of photosynthetic activity in response to changes in carbon and nitrogen availability. RESULTS: In the current study, a mutant Anabaena sp. PCC 7120 strain lacking asr1131 (Δcse) was highly prone to filament fragmentation, leading to a striking phenotype of very short filaments and poor growth under nitrogen-depleted conditions. Transcriptomics analysis under nitrogen-replete conditions revealed that genes involved in heterocyst differentiation and function were downregulated in Δcse, while heterocyst inhibitors were upregulated, compared to the wild-type. CONCLUSIONS: These results indicate that CSE is required for filament integrity and for proper differentiation and function of heterocysts upon changes in the cellular carbon/nitrogen balance. A role for CSE in transmitting Ca(2+) signals during the first response to changes in metabolic homeostasis is discussed.